Consumer Loan Response to Permanent Labor Income Shocks: Evidence from a Major Minimum Wage Increase - Ibrahim Ethem Guney; Yavuz Selim Hacihasanoglu; Semih Tumen (Global Labor Organization (GLO), 2017)
We investigate the impact of a substantial minimum wage increase, which became effective in January 2016, on consumer loans in Turkey. Using bank-level data and designing an original identification strategy, we ask whether the loans provided by banks with a historically high share of low-wage loan customers have increased relative to those provided by banks with a historically low share of low-wage loan customers after January 2016. Our results suggest that consumer loan flows have displayed a limited but statistically and economically meaningful increase following the minimum wage hike. This increase mostly comes from the increase in long-term general-purpose loans. Vehicle loans have also increased, while there is no change in housing loans. In the overall, the minimum wage hike has generated a moderate and transitory increase in the flow of consumer loans extended to low-wage earners in Turkey|perhaps due to delayed consumption effect. Consumption of durables, which can further increase household borrowing capacity through collateralized debt channel, has only slightly and temporarily increased. The underlying long-term trends in the stock of consumer loans have hardly changed.
Keywords: D14; E24; G21; J31; 330; Consumer loans; labor income shocks; minimum wages; triple difference